Lysyl oxidases regulate fibrillar collagen remodelling in idiopathic pulmonary fibrosis - Gavin Tjin; Eric S. White; Alen Faiz; Delphine Sicard; Daniel J. Tschumperlin; Annabelle Mahar; Eleanor P. W. Kable; Janette K. Burgess (The Company of Biologists, 2017)
Idiopathic pulmonary fibrosis (IPF) is a progressive scarring disease of the lung with few effective therapeutic options. Structural remodelling of the extracellular matrix [i.e. collagen cross-linking mediated by the lysyl oxidase (LO) family of enzymes (LOX, LOXL1-4)] might contribute to disease pathogenesis and represent a therapeutic target. This study aimed to further our understanding of the mechanisms by which LO inhibitors might improve lung fibrosis. Lung tissues from IPF and non-IPF subjects were examined for collagen structure (second harmonic generation imaging) and LO gene (microarray analysis) and protein (immunohistochemistry and western blotting) levels. Functional effects (collagen structure and tissue stiffness using atomic force microscopy) of LO inhibitors on collagen remodelling were examined in two models, collagen hydrogels and decellularized human lung matrices. LOXL1/LOXL2 gene expression and protein levels were increased in IPF versus non-IPF. Increased collagen fibril thickness in IPF versus non-IPF lung tissues correlated with increased LOXL1/LOXL2, and decreased LOX, protein expression. β-Aminoproprionitrile (β-APN; pan-LO inhibitor) but not Compound A (LOXL2-specific inhibitor) interfered with transforming growth factor-β-induced collagen remodelling in both models. The β-APN treatment group was tested further, and β-APN was found to interfere with stiffening in the decellularized matrix model. LOXL1 activity might drive collagen remodelling in IPF lungs. The interrelationship between collagen structural remodelling and LOs is disrupted in IPF lungs. Inhibition of LO activity alleviates fibrosis by limiting fibrillar collagen cross-linking, thereby potentially impeding the formation of a pathological microenvironment in IPF.